87 Comparison of functional ability in siblings with duchenne muscular dystrophy. (30th November 2020) - Rye, Catherine; Main, Marion; Muntoni, Francesco
Abstract : Early diagnosis is important to optimise management and prolong function in patients with Duchenne Muscular Dystrophy (DMD). There is little research comparing functional outcomes of siblings diagnosed at different ages. This study aims to analyse the effect of age at diagnosis and prescription of steroids on function in siblings with the same genetic diagnosis of DMD. Functional ability was measured using the North Star Ambulatory Assessment (NSAA) which is a validated outcome measure in ambulant children with DMD. NSAA data from 24 siblings (48 patients) was collected from their first NSAA assessment at Great Ormond Street Hospital, including all scores until July 2020. Age matched NSAA scores were collated at 6 monthly intervals (± 3 months) between 5.5–10.5 years in siblings, where one or more NSAA scores could be compared. 17 siblings (34 patients) met the inclusion criteria and were analysed. Results show that younger siblings were diagnosed on average 2.7 years earlier and started steroids 0.8 years earlier. The median peak NSAA scores were higher in older siblings at ages 5.26–6.25 and 7.26–8.25 years. Between 6.26–7.25 and after 8.26 years, the younger siblings median NSAA scores were consistently higher, although there were small numbers in each sub-group. Wilcoxon Signed Rank test showed no significant differences between groups. Analysis of the graph suggests that despite the earlier age at diagnosis, younger siblings did not diverge from the older sibling in the first phase of the disease. Visual inspection of the NSAA score shows that after 8 years old, the younger siblings consistently scored higher values. This suggests that earlier initiation of steroids is likely to have played a role in this outcome, as previously demonstrated in the DMD population. Further research will assess long-term effects of these trends, regarding age at loss of ambulation, and of respiratory insufficiency.